Seeing Clearly: A Community-Based Inquiry Into Vision Care Access For a Rural Northern First Nation - Brise, Lindsey S; de Leeuw, Sarah (Canadian Journal of Optometry, 2015)
There are a variety of barriers to eye-care service access in rural Northern First Nations communities. Semi-structured, opened-ended key informant interviews were conducted on the topic of eye care, with eight First Nations individuals employed by the health office in a small Northern British Columbian First Nations community. Data analysis comprised identifying themes by analyzing similarities and dissimilarities in participants’ narratives, including comparing and contrasting viewpoints of participants and placing themes within broader sociocultural and historic contexts. Themes identified in the data included the current state of community eye care, facilitators and barriers to accessing eye care, and community needs and preferences. The theme of “facilitators and barriers” was further analyzed, resulting in subthemes of awareness, attitudes, social, economic, and service related. Better understanding of the barriers and their interactions would provide a foundation upon which innovative eye-care programs might be developed.